DEVELOPING DESCRIPTIVE TEXT READING MATERIALS BASED ON CONSTRUCTIVISM APPROACH - Abdul Razak; Hermandra; Elmustian (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research and development aimed to produce descriptive text reading materials based on a constructivism approach. This research was conducted through the following procedures: (1) analyzing needs; (2) designing the product; (3) developing the initial product; (4) conducting a limited trial; (5) revising the product; (6) conducting a large-scale trial; and (7) producing the product (a prototype). The instrument used in this research was a questionnaire addressed to experts, users (Bahasa Indonesia teachers), and the audience (grade VII students of SMP/MTs). In addition, a cloze test was utilized to measure the readability of descriptive texts and the main narration of the learning materials. The development of the materials was carried out based on the five phases of constructivism proposed by Needham. The product trial was conducted in grade VII junior high schools in Kabupaten Lingga, Kepulauan Riau Province, which were not exposed to Covid-19. This study concluded that the developed learning materials were feasible for descriptive text reading materials, and it was expected that these materials would provide a positive contribution to the development of educational science.